2007
DOI: 10.1002/uog.3918
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chromosomal abnormalities, congenital abnormalities and transfusion syndrome in twins

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 24 publications
8
86
3
Order By: Relevance
“…It has been suggested that this sign might constitute an early manifestation of TTTS 3,4 , but this notion has been questioned in more recent studies 5,6,22 . Therefore, it is suggested that this finding in a monochorionic twin should prompt a search for signs of TTTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that this sign might constitute an early manifestation of TTTS 3,4 , but this notion has been questioned in more recent studies 5,6,22 . Therefore, it is suggested that this finding in a monochorionic twin should prompt a search for signs of TTTS.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports suggested an association between increased NT (> 95 th percentile) in one fetus and subsequent development of twin-twin transfusion syndrome (TTTS) 3,4 , but according to recent studies this association is controversial 5,6 . In a recent series of monochorionic twins, a ≥ 20% discordance in NT was found to increase the risk of subsequent fetal demise or severe TTTS to more than 30% 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Twin pregnancies have an increased risk of congenital malformations, especially monochorionic twins (Sperling et al, 2007). Congenital anomalies may be the result of the teratogenic insult responsible for the twinning.…”
Section: Congenital Malformationsmentioning
confidence: 99%
“…The incidence of congenital malformations was 3.2% among monozygotic and 2.2% among dizygotic twins. Cardiac abnormalities accounted for 68% of all abnormalities (Sperling et al, 2007).…”
Section: Congenital Malformationsmentioning
confidence: 99%
See 1 more Smart Citation